KAJIAN YURIDIS KEJAHATAN PENCERNARAN NAMA BAIK MENURUT HUKUM POSITIF DAN HUKUM ISLAM: JURIDICAL STUDY OF THE CRIME DAMAGE ACCORDING TO POSITIVE LAW AND ISLAMIC LAW - Rinda Rinda; Krisna Angga (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
The rapid development of science and technology also has an impact on the development of crime, one of which is the crime of defamation. Defamation is a crime that has its own characteristics that cannot be equated with crimes in general, because it is a special crime that needs to be regulated in a legal system. In positive law this act is regulated in Artides 310-321 of the Criminal Code and also Artide 27 paragraph (3) in conjunction with Artide 45 of the ITE Law. Then in Islamic law this act is induded in jarimah hudud. Normative legal research is legal research used in this research, which is prescriptive in nature by using sources of legal materials, booh primary legal materials and secondary legal materials. The approach used is comparative. The results of the study are that both Positive Law and Islamic Law explicitly regulate acts of defamation, these two legal systems have the same characteristics in determining the qualifications of defamation offenses and criminal liability, the only difference relates to the type of punishment given to the two perpetrators of defamation.